Peran manajemen strategi dalam implementasi Ijarah Muntahiah bi al-Tamlik untuk infrastruktur fisik - Shofiranti, Najwa Ishma (Maliki Interdisciplinary Journal, 2024)
This study examines the role of strategic management in the implementation of Ijarah Muntahiah bi al-Tamlik (IMBT) for physical infrastructure projects. IMBT is an increasingly popular Sharia financing scheme that allows lessees to acquire ownership of assets after the lease period. However, its implementation faces various challenges, making strategic management essential for managing risks and ensuring compliance with Sharia principles. Through a literature review and analysis of previous studies, this research explores key elements of strategic management, including comprehensive planning, effective risk management, coordination with stakeholders, continuous monitoring, and adaptability to change. The findings indicate that effective implementation of strategic management can minimize the risk of project failure, ensure compliance with Sharia principles, and achieve economic objectives. Additionally, this study provides recommendations for stakeholders to enhance the effectiveness of IMBT implementation in infrastructure projects. The results are expected to serve as a reference for developing a better management framework in the future.